2010
DOI: 10.1073/pnas.1004829107
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin regulates corticostriatal inhibitory networks during working memory performance

Abstract: Neurofibromatosis type I (NF1) is one of the most common singlegene causes of learning disabilities. Here, we use behavioral working memory probes and electrophysiological studies in a mouse model of NF1 (Nf1 heterozygous null mutants; Nf1 +/− ) to demonstrate that (i) Neurofibromin regulates prefrontal and striatal inhibitory networks, specifically activity-dependent GABA release and (ii) is required for working memory performance, with inhibitiondependent working memory deficits seen in Nf1 +/− mice. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
155
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 52 publications
26
155
1
Order By: Relevance
“…Lee et al (2014) recently demonstrated that mice expressing either of two NS-associated mutations in PTPN11 show hippocampaldependent impairments in spatial learning tasks as well as deficits in hippocampal long-term potentiation. Other studies have reported that dysregulation of Ras can result in differences in maturation or functioning of frontal-subcortical circuitry involved in attention and cognitive control (Shilyansky et al 2010a). In a study of humans, Mainberger et al (2013) reported that, relative to a healthy comparison group, individuals with NS show reduced motor cortex plasticity (measured by changes in motor evoked potential amplitude) in response to paired peripheral electrical and transcranial magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al (2014) recently demonstrated that mice expressing either of two NS-associated mutations in PTPN11 show hippocampaldependent impairments in spatial learning tasks as well as deficits in hippocampal long-term potentiation. Other studies have reported that dysregulation of Ras can result in differences in maturation or functioning of frontal-subcortical circuitry involved in attention and cognitive control (Shilyansky et al 2010a). In a study of humans, Mainberger et al (2013) reported that, relative to a healthy comparison group, individuals with NS show reduced motor cortex plasticity (measured by changes in motor evoked potential amplitude) in response to paired peripheral electrical and transcranial magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has indicated that Ras proteins (which are abnormally activated in these syndromes) may regulate interneuronal activity in prefrontal and striatal networks (Shilyansky et al 2010a). These regions of the brain are known to be critical for a number of higher-order cognitive processes such as working memory, response inhibition, and cognitive flexibility (Powell and Voeller 2004).…”
Section: Attention and Executive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with a heterozygous inactivating mutation in the Tsc genes (Tsc1 +/− and Tsc2 +/− mice) show deficits in learning, memory and contextual fear conditioning [56,68]. In addition to learning and memory deficits, Tsc1 +/− mice have reduced levels of social exploration, while Tsc2 +/− knockout mice show a normal social behavior [68,128] but altered ultrasonic vocalization [153]. In addition to behavioral changes, synaptic abnormalities are observed in the hippocampus of Tsc2 +/− and in mice with a conditional homozygous deletion of Tsc1 in astrocytes [56,68].…”
Section: Tsc1/2mentioning
confidence: 99%
“…However, findings of brain abnormalities such as reduced white matter integrity, macrocephaly, abnormal gamma-aminobutyric acid activity, among others have provided converging evidences for impaired communication between the neural regions, and early myelin dysfunction in NF1 has been hypothesized to underlie cognitive deficits. In addition, the NF1 cognitive profile may be related with independently inherited genetic modifiers 30 and all cognitive impairments are considered a major source of decreased quality of life in NF1 childhood 31 .…”
Section: Nf1 Cognitive and Behavioral Featuresmentioning
confidence: 99%